Effect of Funding Decisions on Firm Value with Profitability as Intervening Variables - Asrini Wahyuni; Syamsu Alam; Erlina Pakki (Hasanuddin Journal of Business Strategy, 2020)
This study aims to determine the effect of funding on firm value where profitability acts as a mediator or intervening variable in manufacturing companies on the Indonesia stock exchange. Funding variables are measured using Debt to Assets Ratio (DAR) and Debt to Equity Ratio (DER). The profitability variable is measured using Return of Assets (ROA). The value of the company itself is measured by looking at the Price to Book Value (PBV) or the market value of the company's shares against the book value ( Book Value ). The population in this study is the pharmaceutical sub-sector manufacturing companies listed on the IDX. The sampling method used was purposive sampling. The data source used in this study is secondary data collected using documentation techniques. This study uses descriptive quantitative statistics and uses panel data regression which is processed using Eviews 11 software. The results obtained in this study indicate that first, DER has a positive and significant effect on ROA. Second, DAR has a negative and significant effect on ROA. Third, DER has a positive and significant effect on ROA. Fourth, DAR has a negative and not significant effect on PBV. Fifth, ROA has a positive and significant effect on PBV. Sixth, DER has a positive and significant effect on PBV through ROA. Seventh, DAR has a negative and significant effect on PBV through ROA.